Synchronized assembly of the oxidative phosphorylation system controls mitochondrial respiration in yeast - Moretti-Horten, Daiana; Peselj, Carlotta; Taskin, Asli Aras; Myketin, Lisa; Schulte, Uwe; Einsle, Oliver; Drepper, Friedel; Luzarowski, Marcin; Vögtle, Friederike-Nora (Developmental cell, 2024)
Control of protein stoichiometry is essential for cell function. Mitochondrial oxidative phosphorylation (OXPHOS) presents a complex stoichiometric challenge as the ratio of the electron transport chain (ETC) and ATP synthase must be tightly controlled, and assembly requires coordinated integration of proteins encoded in the nuclear and mitochondrial genome. How correct OXPHOS stoichiometry is achieved is unknown. We identify the Mitochondrial Regulatory hub for respiratory Assembly (MiRA) platform, which synchronizes ETC and ATP synthase biogenesis in yeast. Molecularly, this is achieved by a stop-and-go mechanism: the uncharacterized protein Mra1 stalls complex IV assembly. Two “Go” signals are required for assembly progression: binding of the complex IV assembly factor Rcf2 and Mra1 interaction with an Atp9-translating mitoribosome induce Mra1 degradation, allowing synchronized maturation of complex IV and the ATP synthase. Failure of the stop-and-go mechanism results in cell death. MiRA controls OXPHOS assembly, ensuring correct stoichiometry of protein machineries encoded by two different genomes.